Status epilepticus in pediatric patients severity score (STEPPS) as an outcome predictor in children - Niken Iswarajati; Intan Fatah Kumara; Agung Triono (Indonesian Pediatric Society, 2022)
Background Status epilepticus (SE) is a neurological emergency, with short-term mortality ranging from 0.9 to 3.6% in children. The disease burden of SE includes morbidity, treatment costs, and mortality. Various scoring tools for predicting outcomes in adult SE cases have been widely studied, but there are few tools for predicting outcomes in children with SE. Objective To evaluate the usefulness of status epilepticus in pediatric patients severity score (STEPSS), a clinical score for predicting functional outcome and mortality in pediatric patients with status epilepticus, as well as to identify characteristics of SE patients. Methods This retrospective cohort study included 88 pediatric patients with status epilepticus aged >1 month to ?18 years by consecutive sampling, who were treated at Dr. Sardjito Hospital, Yogyakarta. All subjects underwent assessment by STEPPS score, which were compared to functional outcome assessed by Pediatric Overall Performance Capacity (POPC) score and mortality. Results STEPPS > 3 was significantly correlated with poor functional outcome (OR 2.85; 95%CI 1.04 to 7.87; P=0.043), but was not significantly correlated with mortality outcome in children with SE (P=0.411). Conclusion STEPPS score with cut-off >3 can be used as a predictor of poor functional outcome in pediatric patients with SE aged >1 month to ?18 years, but cannot be used as a predictor of mortality.